Hepatitis B Viral Load Monitoring Insight Across India: Needs Lucidity on Burden of Silent Killer - Nikam, Chaitali; Sengupta, Caesar; Ganesan, Praveenkumar (Asian Journal of Biological and Life Sciences)
Background: Hepatitis B virus (HBV) infection is one of the most serious infectious diseases that needs a critical attention in India. The current study aims to estimate the prevalence of the seropositive patients to assess the burden of the disease. Methods: Blood samples were collected from 14,440 individuals for the diagnosis of hepatitis B surface antigen using the real-time PCR quantification between July 2017 to July 2018. Results: The mean age of the participants is 36.9 ± 14.4 in years. In total, 9657 (67%) were found to be positive for HBV infection and positivity was higher in males than females (63% vs. 37%) (odds ratio (OR)=1.10;95% CI;1.031-1.189). The highest Hep B prevalence was 50.8% in adult (19-49 years) age group and the lowest were 0.2% in less than 6 year age. Conclusion: The adult population is most commonly affected and this raises the alarm to take stringent infection-control measures to prevent the spread of HBV infection in the population.
Keywords: HBV prevalence; HBV viral load; Hepatitis; Hepatitis B Virus; India; Seropositive